2008
DOI: 10.1016/j.ejcts.2007.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of analgesic quality in the postoperative of thoracotomy: paravertebral block with bupivacaine 0.5% vs ropivacaine 0.2%☆

Abstract: Post-thoracotomy analgesia combining paravertebral catheter and a nonsteroidal anti-inflammatory drug is a safe and effective practice, VAS values are acceptable (only 16% of patients required meperidine as rescue). It prevents the risk of side effects related to epidural analgesia. Patients submitted to AT experienced less pain than those with PT (4.5 vs 5.9, p<0.01). Bupivacaine got slightly better VAS values than ropivacaine (4.9 vs 5.4 p<0.05). Higher doses and volumes of local anesthetic could be used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 21 publications
1
24
0
3
Order By: Relevance
“…Regarding the safety profile, ropivacaine has a lower potential to induce cardiovascular and neural toxicity in comparison to bupivacaine [8,9] due to the fact that it is a pure S-enantiomer instead of a racemic bupivacaine [5]. Besides a reliable intraoperative anesthetic effect, a long-lasting postoperative analgesia was repeatedly reported for both ropivacaine and bupivacaine used for peripheral nerve blocks and infiltration [6,[10][11][12][13] or epidural anesthesia [7,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the safety profile, ropivacaine has a lower potential to induce cardiovascular and neural toxicity in comparison to bupivacaine [8,9] due to the fact that it is a pure S-enantiomer instead of a racemic bupivacaine [5]. Besides a reliable intraoperative anesthetic effect, a long-lasting postoperative analgesia was repeatedly reported for both ropivacaine and bupivacaine used for peripheral nerve blocks and infiltration [6,[10][11][12][13] or epidural anesthesia [7,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The use of intermittent bolus doses of local anesthetics or continuous infusion of local anesthetics through a paravertebral catheter was considered for post-thoracotomy pain relief with or without the use of additional systemic opioids [5].…”
Section: Introductionmentioning
confidence: 99%
“…In our group, we have a large experience in the use of PVC for post-thoracotomy analgesia [11,12]. We have demonstrated that its placement is technically simple and safe.…”
Section: Discussionmentioning
confidence: 96%
“…Direct placement of a PVC in the paravertebral space in VATS surgery has been considered technically too difficult, and has not been routinely performed [9,10]. Since 2002, in our Department we have been employing a multimodal treatment of post-thoracotomy pain consisting of a PVB through a PVC inserted during surgery with a bolus of a local anesthetic (ropivacaine 0.2%) combined with an NSAID (metamizol) with excellent results [11,12].…”
Section: Introductionmentioning
confidence: 98%